Respuesta :

Answer:

Multiply the second equation by -3 to get -3x - 9y = -30.

Step-by-step explanation:

When eliminating, you need to find a term with the negative of that term to combine so that they cancel each other out. An example would be 3x in the first equation and (-3x) in another equation so that when added, it becomes: 3x-3x = 0.

In the second equation, you see that there is already an x there and you just need to make it become (-3x). Thus, you multiply the entire second equation by -3 to make -3x. Once you have done that, you can combine the two equations and eliminate 3x from the first equation.

3x + 5y = 30

-3x - 9y = -30

3x + 5y -3x - 9y = 30 + (-30)

0 - 4y = 30 - 30

-4y = 0

You can find y and then x later on from here.